2019
DOI: 10.35794/jpekd.15775.19.1.2017
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Faktor-Faktor Yang Mempengaruhi Jumlah Kunjungan Dan Nilai Ekonomi Kebun Raya Bogor

Abstract: ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI JUMLAH KUNJUNGAN DAN NILAI EKONOMI KEBUN RAYA BOGORYuzuardi Haban, Rosalina A.M. Koleangan, George M.V. KawungFakultas Ekonomi dan Bisnis, Magister Ilmu EkonomiUniversitas Sam Ratulangi, ManadoABSTRAK Penelitian ini memiliki dua tujuan, tujuan yang pertama untuk mengetahui pengaruh faktor-faktor yang diduga mempengaruhi jumlah kunjungan individu ke Kebun Raya Bogor dengan menggunakan analisis regresi berganda, faktor-faktor tersebut antara lain biaya perjalanan (travel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 1 publication
2
2
0
3
Order By: Relevance
“…That is, the higher the costs incurred to visit the TWAW, the smaller the number of visits. These results are in line with the results of research by Haban et al (2019); and Oby & Suhartini (2016). This is due to the status of TWAW which is known as a cheap tourist attraction with a close location and easy accessibility because it can be reached by public transportation or other transportation so it is very easy to reach.…”
Section: The Effect Of Travel Costs On the Number Of Individual Visitssupporting
confidence: 92%
See 2 more Smart Citations
“…That is, the higher the costs incurred to visit the TWAW, the smaller the number of visits. These results are in line with the results of research by Haban et al (2019); and Oby & Suhartini (2016). This is due to the status of TWAW which is known as a cheap tourist attraction with a close location and easy accessibility because it can be reached by public transportation or other transportation so it is very easy to reach.…”
Section: The Effect Of Travel Costs On the Number Of Individual Visitssupporting
confidence: 92%
“…In line with the results of this study, research conducted by Shelvatis et al (2017) also proves that individual income does not have a significant effect on tourist visits. Meanwhile, research conducted by Haban et al (2019); Oby & Suhartini (2016) found different results. Keynes's theory of consumption explains that when an individual's income increases, the level of consumption also tends to follow and vice versa.…”
Section: Individual Travel Cost Methods (Itcm)mentioning
confidence: 99%
See 1 more Smart Citation
“…sesuai dengan Vidi dan Misi Garut mewujudkan Garut sebagai daerah pariwisata disertai pelestarian dan pengembangan seni budaya lokal dan memberdayakan sistem ekonomi kerakyatan yang bertumpu pada potensi lokal dan mekanisme pasar. Banyaknya tempat objek wisata Garut seperti Cipanas, Situ Bagendit, Candi Cangkuang, Pantai Santolo merupakan tujuan wisata yang sering kali dikunjungi oleh wisatawan, [31].…”
Section: Hasil Dan Pembahasanunclassified
“…Diluar karakteristik di atas, tingkat pendidikan responden merupakan salah satu faktor yang dapat mempengaruhi persepsi seseorang terhadap suatu sarana wisata (Haban et al, 2017). Studi ini tidak melihat tingkat pendidikan responden karena faktor ini sebelumnya telah diteliti oleh Situmorang et al (2020).…”
Section: Gambar 4 Karakteristik Responden Berdasarkan Daerah Asalunclassified